Simulation Scenarios for Deploying Underwater Safe-Net Sensor Networks Using Remote Operated Vehicles: Offshore Exploration Constructions Models and Sensor Deployment Methods - Caraivan, Mitrut; Dache, Valentin; Sgârciu, Valentin (2013 19th International Conference on Control Systems and Computer Science, 2013)
This paper is following the development of the PhD research of Optimizing Real-Time Applications for Marine Operations Using Modern Modelling and Simulation Methods and presents the major challenges in designing simulation scenarios for offshore exploration constructions models and furthermore, some sensor deployment methods using remote operated vehicles (ROY).